Gluten Rice Cultivation and Business in Malaysia: A Social Entrepreneurship Approach in Agent-Structure Analysis - Alia Fateha binti Zahari; Lubis, Ahmad Sayyidulhaq Arrobbani Lubis (Journal of Peasants' Rights, 2024)
The cultivation of gluten rice in Malaysia is growing with global market demand, creating social entrepreneurship opportunities that empower farmers and offer sustainable social, economic and environmental impacts. The main objective of this study is to analyze gluten rice cultivation and business in Malaysia through a social entrepreneurship approach using agent-structure analysis, where the interactions between key agents such as farmers, social entrepreneurs, government, and consumers, as well as the social, economic, and policy structures that influence them, are analyzed to understand their role in shaping a sustainable and competitive gluten rice industry. The research method used is a literature review with a methodological approach involving identification, analysis and synthesis of literature. Data collection techniques were conducted by utilizing various sources such as books, academic journals, research reports, and articles related to social entrepreneurship, actors in networks, and social value production. The data analysis technique used was descriptive qualitative. Based on the research on gluten rice cultivation in Malaysia with a social entrepreneurship approach through agent-structure analysis, the main conclusions include several important points. First, the roles of key agents such as farmers, social entrepreneurs and consumers shape the supply chain that supports business sustainability. Second, social, economic and policy structures, including green regulations and market access, influence industry. Third, the gluten-free rice business provides economic and social benefits, improving farmers' incomes and supporting healthy lifestyles. Finally, sustainable agricultural practices support environmental sustainability and carbon footprint reduction.